The Effect of the Four Pillars Strategy on the Achievement of Middle-Grade Students with Biology and the Ability to Decision Making - Al-Saray , Ahmed Jassem Khowait; Abdullah, Kefah Mohsen (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to: Identify: (The effect of the four pillars strategy on the achievement of middle- grade second-year students with biology and the ability to Decision Making). To verify the research goal, the following two hypotheses were formulated: There is no statistically significant difference at the level of significance (0.05) between the average achievement levels of students studying according to the four pillars strategy and the average score of students studying according to the usual method. There is no statistically significant difference at the level of significance (0.05) between the average decision-making degrees for students who study according to the four pillars strategy and the average degrees of students who study according to the usual method. The research sample consisted of (86) students with (43) students for the experimental group and (43) students for the control group from the second year middle school students in science high school for boys, and the two groups were rewarded with variables (academic achievement, previous information, intelligence, and decision-making), and identified the article Of scientific studies in the seven chapters of biology subject, 2nd edition of 2018, teaching plans have been prepared for the two research groups, and the behavioral purposes of the scientific subject classes, which numbered (167), have been behavioral purpose according to the six levels of Bloom’s classification respectively (remembering, assimilation, application, analysis, composition, Calendar), and a sister was prepared A summary consisting of (40) objective items of the multiple choice type, a decision-making scale has been prepared that consists of (80) items formulated on (20) problems, and after completing the teaching of the scientific subject for the two research groups applied the two tests (achievement and decision making) after If the psychometric properties of the two variables were confirmed, then: The experimental group outperformed the control and decision-making group over a statistically significant difference.